The impact of India's rural employment guarantee on demand for agricultural technology - Bhargava, Anil K. (International Food Policy Research Institute, 2014)
This paper investigates whether this increase in the opportunity cost of agricultural labor incentivizes farm owners to adopt labor-saving agricultural technology. Using a regression discontinuity design and new Indian agricultural census data, this paper finds that NREGA causes a shift of roughly 20 percentage points away from labor-intensive technologies toward labor-saving ones, particularly for small farmers and low-powered technologies.